Background and Literature Review of Global Value Chains - Sourish Dutta (ZBW - Leibniz Information Centre for Economics, 2018)
The phenomenon of global value chains (GVCs) indicates a division of labour type production structure in which tasks and business functions are distributed among several companies, globally, or regionally (Grossman and Rossi-Hansberg 2008). The critical features of GVCs are therefore the international dimension of the production process and the "contractualisation" of buyer and seller relationships, often across international borders (Antras 2016). As a result, these international production networks are highly complex regarding geography, technology, and the different types of firms involved (from large retailers and highly large-scale mechanised manufacturers to small home-based production). Sometimes it may be impossible even to identify all the countries that are involved or the extent of their involvement (Gereffi and Fernandez-Stark 2016). However, the recent development of OECD-WTO's Trade-in Value Added (TiVA) data represents a fundamental step forward in understanding GVC trade. Grossman & Rossi-Hansberg (2008, 2012) rightly point out that the different tasks, rather than sectors, define the specialisation of countries in the value chains.
Keywords: F0; F1; F2; 330; Global Value Chains; International Trade; Global Production Network